DAMPAK TEKNOLOGI AGRICULTURE GROWTH PROMOTING INOCULANT (AGPI) PADA USAHATANI PADI SAWAH DI KABUPATEN SLEMAN - Ken Suratiyah (Agro Ekonomi, 2010)
This research was carried out in the Margo Agung villagem Seyegan subdistrict, Sleman regency, which aims (1) to identify how farmers use AGPI technology in rice farming, (2) to know the production, sot, incomes of farmers, (3) to analyze feasibility of rice farming and social prospect that includes the performance of farmer groups in implementing AGPI technology. The basic method in this study is descriptive analytical. The population are farmers who have applied AGPI technology on rice farming in the Sleman Regency, while the respondents were 30 farmers who are members of the farmers grup of Agung Bergas and Sumber Rejeki, in Margo Agung village, Seyegan Subdistrict. The result shows that (1) implementation of AGPI technology, the role of farmer groups as medium of learning, collective decision making and production unit tend to be higher, (2) AGPI technology increase the total cost and labour but yields enhancement in rice production and income, (3) AGPI technology increase implementation is feasible, showed by the R/C>1, income > rental cost, π/C > bank interest, labor productivity > UMK, production, revenue, and the production prices > BEP.